INTELLECTUAL PROPERTY: CATEGORIAL DEVICE AND INSTITIONAL DEVELOPMENT - ANZHELIKA PETROVNA Buevich (Мир новой экономики)
The author of article raises the questions of terminology of the sphere of intellectual activity that is especially actual in the conditions of economy of knowledge. Today forming of the general-theoretical approach promoting further formation of large-scale sector of national and world economy is necessary. Shortcomings of the legislation existing today of the sphere of intellectual activity are noted and the conclusion is drawn on needof conceptualization of intellectual activity and development of the fundamental unified categories of thesetheory, including at the legislative level.